2008
DOI: 10.1002/ijc.23656
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of integrin αυβ6 by RNA interference in colon cancer cells inhibits extracellular matrix degradation through the MAPK pathway

Abstract: Integrin atb6 plays a very important role in the progression of colon cancer cells and is now defined as a novel, independent prognostic indicator for aggressive colon cancer in humans. Herein, we use the RNA interfering technology to downregulate the expression of atb6 in colon cancer cells. Our data demonstrate that plasmid vector based shRNA can effectively down-regulate atb6 expression in protein and mRNA levels. Supression of integrin atb6 inhibits the phosphorylation and nonphosphorylation level of ERK1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…HT-29 cells constantly express ITGB6. HT-29 cells with siRNA suppressed ITGB6 expression were also prepared as reported previously (25). The cells were maintained as monolayers in medium comprising DMEM (Hyclone) containing 10% heat inactivated FCS (Gibco) and supplemented with 20 mmol/L HEPES, 100 IU/mL penicillin, and 100 mg/mL streptomycin.…”
Section: Cell Linesmentioning
confidence: 99%
“…HT-29 cells constantly express ITGB6. HT-29 cells with siRNA suppressed ITGB6 expression were also prepared as reported previously (25). The cells were maintained as monolayers in medium comprising DMEM (Hyclone) containing 10% heat inactivated FCS (Gibco) and supplemented with 20 mmol/L HEPES, 100 IU/mL penicillin, and 100 mg/mL streptomycin.…”
Section: Cell Linesmentioning
confidence: 99%
“…Recently, integrin mediated intracellular signal transduction has been reported to also regulate various cytoplasmic proteins, such as phosphatidylinositol-3 kinase (PI3K) [32,33], the serine-threonine kinase AKT, and the mitogen-activated protein kinase/extracellular regulated kinase (MAPK/ERK) [34,35]. Additionally, integrin ligand binding has been reported to activate focal adhesion kinase (FAK), integrin-linked kinase (ILK), and Src kinases that are related to EMT [36][37][38].…”
Section: Canonical Pathway Analysis Using Metacore™mentioning
confidence: 99%
“…Matrix metalloproteinase (MMP)‐2 and MMP‐9 were also reported to play a role in tumor progression, invasion, and metastasis . Additionally, our previous research had found that suppression of integrin β6 inhibited the phosphorylation and non‐phosphorylation level of extracellular regulated protein kinases (ERK)1/2, the secretion of uPA, pro‐MMP‐9, and pro‐MMP‐2 in tumor conditioned medium, and, most importantly, inhibited mitogen‐activated protein kinase‐dependent labeled collagen IV degradation via the plasminogen activation cascade . The purpose of this study was to discuss the relationship of integrin β6, MMP‐2, and MMP‐9 expression levels in clinical characteristics of human follicular thyroid carcinomas.…”
Section: Introductionmentioning
confidence: 98%